Time Orient Trust Based Hook Selection Algorithm for Efficient Location Protection in Wireless Sensor Networks Using Frequency Measures - Prasanna, D; Santhosh, R (International Journal of Engineering and Technology, 2018)
The presence of heavy adversary in the sensor network threats the quality of service hugely. To overcome the problem of location threat, a time orient trust based approach is presented in this paper. The method handles both source and sinks privacy by selecting random hook points around the region. The method identifies the list of sensors around its location and selects a single sensor as hook point based on the trust measure. The trust measure is estimated based on the participation of the sensor in other transmission and according to the energy parameters of the sensor node. The method uses two way protocols for route discovery.In the route discovery the hook point sends the route reply to the source node, which denotes a different route to be used. Similarly, the hook point fluctuates at each interval according to the frequency measures. For each hook point, the method computes the frequency measure based on the number of transmissions involved and the amount of data being received. The dynamic changing of hook point reduces the impact of heavy Eavesdroppers and improves the QoS of the network.Â Â
Keywords: WSN; Eavesdrop attack; location protection; hook selection; trust based selection; frequency measures; QoS.